Consistency of The Arrangements Granting Extensions of The Term of Building use Rights for Houses to Provide Legal Certainty - Putra Pangestu, Hendy; Koeswahyono, Imam; Sri Kawuryan, Endang (Audito Comparative Law Journal (ACLJ), 2024)
There is ambiguity in the regulation for granting HGB term extensions. Article 35 of the UUPA do not recognize the granting of an extension "all at once", whereas in Article 145 of Law Act No. 6 / 2023 provides provisions for granting extensions “all at once”. There are two problems focuses. First, how are the current regulations regarding granting term extensions? Second, what will be the future regulations regarding granting an extension of the term of building use rights for flats that will provide more legal certainty? The main purpose in this research is to analyses inconsistency about the regulation on HGB. Using normative legal research, with statute approach and conceptual approach. The result in this research, current regulations for granting HGB periods, it turns out that there is a lack of clarity in the regulations. Moreover, what is regulated in Article 145 Law Act No. 6 / 2023 is not in line with Article 33 paragraph (3) UUD NRI 1945. Therefore, future regulations must be developed with linear consistency with the regulatory direction of Article 33 paragraph (3) of the UUD NRI 1945, UUPA, and even the Constitutional Court jurisprudence to provide legal certainty.